Isolation of Salt Stress-Related Genes from Aspergillus glaucus CCHA by Random Overexpression in Escherichia coli - Jie Fang; Xiaojiao Han; Lihua Xie; Mingying Liu; Guirong Qiao; Jing Jiang; Renying Zhuo (The Scientific World Journal)
The halotolerant fungus Aspergillus glaucus CCHA was isolated from the surface of wild vegetation around a saltern with the salinity range being 0–31%. Here, a full-length cDNA library of A. glaucus under salt stress was constructed to identify genes related to salt tolerance, and one hundred clones were randomly selected for sequencing and bioinformatics analysis. Among these, 82 putative sequences were functionally annotated as being involved in signal transduction, osmolyte synthesis and transport, or regulation of transcription. Subsequently, the cDNA library was transformed into E. coli cells to screen for putative salt stress-related clones. Five putative positive clones were obtained from E. coli cells grown on LB agar containing 1 M NaCl, on which they showed rapid growth compared to the empty vector control line. Analysis of transgenic Arabidopsis thaliana lines overexpressing CCHA-2142 demonstrated that the gene conferred increased salt tolerance to plants as well by protecting the cellular membranes, suppressing the inhibition of chlorophyll biosynthesis. These results highlight the utility of this A. glaucus cDNA library as a tool for isolating and characterizing genes related to salt tolerance. Furthermore, the identified genes can be used for the study of the underlying biology of halotolerance.